JAPANESE FORMS OF "OBLIGATION" AND "ADVICE": ANALYSIS OF SHOULD, MUST, BETTER (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article examines three Japanese grammar forms — 〜べき (should), 〜なければならない (must), 〜ほうがいい (better to). It analyzes their similarities and differences in expressing obligation, recommendation, and advice. The meaning, usage context, and level of formality of each form are illustrated with examples. This article helps learners understand which form is appropriate in different situations and serves as a practical guide for correctly using Japanese grammar forms.